Perancangan dan Implementasi Backend Website Company untuk PT. Sarana Bangun Sejati - Deric Cahyadi; Eryc; Indasari Deu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2025)
This study aims to design and implement a corporate profile website for PT Sarana Bangun Sejati as a digital media to enhance company image and communication in the digital era. Using needs analysis via interviews and observations, the website was designed with HTML, CSS (Bootstrap 5), JavaScript, and PHP, developed through the Agile Scrum method with three weekly sprints. The resulting responsive and interactive website features contact forms and project galleries, supporting digital marketing and facilitating communication with customers and partners. It is recommended that the company regularly updates content through the backend system and considers additional features for long-term development.